Toward the Allelopathy of Peganum sp. and Related Chemical Constituents in Agriculture - Bitchagno, Gabin Thierry M.; El Bouhssini, Mustapha; Mahdi, Ismail; Ward, Jane L.; Sobeh, Mansour (Frontiers in Plant Science, 2022)
The genus Peganum constitutes one of the perennial groups of plants of semi-arid regions across the World. It produces diverse classes of metabolites with claimed valuable pharmacological applications. Despite the key chemical and biological properties of the genus, its allelopathy or that of one of its species, has not been reviewed yet. Thus, the present survey aims to report the agricultural applications of extracts, fractions, and compounds from the genus Peganum. This work was based on the available literature related to both the Peganum genus and agriculture which were generated from available high-impact scientific engines. The plants in this genus contain a large group of secondary metabolites including phenolic compounds, terpenes, and N-containing compounds. Alkaloids, as the main components of the extracts from plants in the genus, were identified as the major active principles. The toxicity of Peganum isolates against plants and related pest organisms was also reviewed. Extract preparations from species of Peganum were listed among insecticidal and herbicidal allelochemicals used for crop protection. The review also tried to contextualize natural products in agriculture. Peganum plant extracts, and fractions have showed significant potential in weed and crops management, soil health and biopesticide production.